Can introduced and indigenous rhizobial strains compete for nodule formation by promiscuous soybean in the moist savanna agroecological zone of Nigeria? - Okogun, J.A.; Sanginga, N. (Springer, 2003)
Promiscuous soybean lines have been bred on the basis that they would nodulate freely without artificial inoculation. However, our recent studies have demonstrated that the indigenous rhizobia are not able to meet their full nitrogen (N) requirement. Rhizobia inoculation might be necessary. We examined the competition for nodule formation among native Rhizobia spp. and two inoculated Bradyrhizobia strains (R25B indigenous strain and a mixture of R25B+IRj 2180A indigenous strain from soybean lines in the savanna of northern Nigeria), their effect on N fixation, and their contribution to the yield of four soybean cultivars, grown in the field in three different agroecological zones in the moist savanna of Nigeria. About 34% of nodules were formed by the mixture of introduced R25B+IRj 2180A, while R25B formed only about 24% of the nodules but did not influence biomass and grain yield production. The indigenous rhizobia strains that nodulated the soybean varieties fixed up to 70% of their accumulated total N, confirming the promiscuous nature of these soybean varieties. Even though these varieties fixed about 75 kg N ha1; this was not enough to sustain their optimum grain yield, as earlier reported. However, the grain yield from inoculated soybean was not significantly higher than that from the uninoculated soybean, showing a degree of competitiveness among the introduced rhizobial strains and the native rhizobia population.